O Come, Let Us Worship : Corporate Worship in the Evangelical Church - Rayburn, Robert Gibson, 1915- (Grand Rapids, Mich. : Baker Book House, 1980)
Reacting to formless consumerism and reaching for the best of church tradition, Robert G. Rayburn became the vanguard of these modern integrative liturgies. His 1980 O Come, Let Us Worship sought to re-introduce evangelicalism to its history and liturgy. His order of service was a perceptive summary of North American traditions birthed in frontier revivalism combined with a respectful reiteration of Westminster Puritanism. The effect was an intentional honoring of Calvinistic roots and an instinctive echoing of more distant patristic (i.e., ancient Catholic) practices in a worship context dominated by forms of evangelicalism that venerated spontaneity over form. - Bryan Chapell.
The importance of worship -- Corporate worship in the Old Testament -- Corporate worship in the New Testament -- The nature and manner of true worship -- General considerations concerning the order of worship -- The order of common worship -- The order of common worship, continued -- Hymnody in the church -- The administration of the sacraments -- The wedding service -- The funeral service -- Supplement : Aids for the preparation of corporate worship services. Calls to worship -- Before confession -- Corporate confessions of sin -- Scriptural confessions -- Assurances of pardoning grace -- Before the offering -- Before a hymn of praise -- Before prayer -- Before reading the scripture.
Keywords: Public worship; Worship - Christian - Introduction